Anticholinesterase activity of Areca Catechu: In Vitro and in silico green synthesis approach in search for therapeutic agents against Alzheimer's disease - Sushma Pradeep; Samudyata C. Prabhuswaminath; Pruthvish Reddy; Sudhanva M. Srinivasa; Ali A. Shati; Mohammad Y. Alfaifi; Serag Eldin I. Elbehairi; Serag Eldin I. Elbehairi; Raghu Ram Achar; Ekaterina Silina; Ekaterina Silina; Victor Stupin; et al. (Frontiers Media S.A., 2022)
For many years, the primary focus has been on finding effective treatments for Alzheimer's disease (AD), which has led to the identification of promising therapeutic targets. The necessity for AD stage-dependent optimal settings necessitated a herbal therapy strategy. The plant species Areca Catechu L. (AC) was selected based on the traditional uses against CNS-related diseases. AC leaf extract were prepared using a Soxhlet extraction method and hydroxyapatite nanoparticles (HAp-NPs) were synthesized from the same (AC-HAp-NPs). Powder X-ray diffractometer (XRD), scanning electron microscopy (SEM), transmission electron microscopy (TEM), selected area electron diffraction (SAED) and fourier transform infrared spectroscopy (FTIR) were used to confirm the structure and morphology of the as-prepared AC-HAp-NPs. The crystalline character of the AC-HAp-NPs was visible in the XRD pattern. The synthesized material was found to be nanoflake, with an average diameter of 15-20 nm, according to SEM analysis. The TEM and SAED pictures also revealed the form and size of AC-HAp-NPs. In vitro anti-acetylcholinesterase and butyrylcholinesterase (AChE and BChE) activities of hydroxyapatite nanoparticles produced from an AC leaf extract was tested in this study. When compared to control, AC-HAp-NPs had higher anti-AChE and BChE activity. The anti-acetylcholinesterase action of phytoconstituents generated from AC leaf extract was mediated by 4AQD and 4EY7, according to a mechanistic study conducted utilizing in silico research. The global and local descriptors, which are the underpinnings of Conceptual Density Functional Theory (CDFT), have been predicted through the MN12SX/Def2TZVP/H2O model chemistry to help in the comprehension of the chemical reactivity properties of the five ligands considered in this study. The CDFT experiments are supplemented by the calculation of several useful calculated pharmacokinetics indices, their expected biological targets connected to the bioavailability of the five ligands in order to further the goal of studying their bioactivity.